Hydrogels Augmented With Artificial Sweeteners can Inhibit Multidrug‐Resistant Acinetobacter baumannii Growth and Biofilm Formation While Demonstrating Safety in Pre‐Clinical Pilot Human Trials - Jie Han; Mohamed Soliman; Bin Zhang; Dominika Krawiel; Ronan R. McCarthy (Advanced Healthcare Materials, 2026)
ABSTRACT There is a critical need for novel therapeutic strategies to tackle multidrug‐resistant bacterial infections. Artificial sweeteners (AS) specifically acesulfame potassium, sodium saccharin, and sodium cyclamate, have recently demonstrated antimicrobial activity against multidrug‐resistant bacteria. In this study, polyvinyl alcohol (PVA)‐borate hydrogel is developed as a carrier for antimicrobial AS to combat wound infections. Through extensive optimization, we developed cytocompatible 8% AS‐loaded hydrogels with 3% PVA + 3% borax that reduced the viability of multidrug‐resistant Acinetobacter baumannii AB5075 by 99.9% colony‐forming unit enumeration following 1 h hydrogel treatment. Most currently available wound dressings have limited efficacy against bacterial biofilms, but we demonstrate that each of these sweeteners can attenuate A. baumannii and Pseudomonas aeruginosa dual‐microbial biofilms. Haemolysis and cell viability assays demonstrate excellent blood compatibility and non‐cytotoxic behavior of the sweetener‐loaded hydrogels. To further evaluate the clinical potential of these AS‐loaded hydrogels, we conducted a pilot Phase I clinical study with human volunteers focused on evaluating short‐term safety and irritancy. This study revealed that the dressings had no adverse effects on the volunteers. This research underscores the translational potential of hydrogels augmented with AS and their capacity to overcome many of the hurdles that typically lead to wound dressing failure.